(3TQM GdCUhd GdNeSIs - (3YHO GdLHGQ Hf CMeO GdgePGfj GdGSJQGHGOj,J (B415 (3g` s ((3ecI GdecQeI s)
(3ChdgG (B:s
(3Edi GdgQH dhbY efg GdgQH dCf GdedLC gh ef HdZ Hg OGYjI LOGdkG dGjbGHdg OGY BNQ s
(3BNQgG (B:s
(3hjOd Ydjg CjVkG bhdg Udi Gddg Ydjg hSde (B:" (3GdEjeGf HVY hSHYhf NUdI CYdGgG cdeI dG Edg EdG Gddg , hCOfGgG EeGWI GdCPi Yf GdWQjb hbhdg Udi Gddg Ydjg hSde (B:" (3Hfi GdESdGe s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds